Query expansion for document retrieval using wordnet / Mohd Hafiz Hussin - Hussin, Mohd Hafiz (2010)
This paper describes the experimentation conducted to test the effectiveness of query expansion. Several experiments generating queries extracted from WordNet. Results show that lexical expansion is not able to improve retrieval performance. Nevertheless, the experiments allow us to conclude that query expansion can benefit searching process which allows structured queries.